Cover Story: La copertina del nuovo numero e un omaggio a VerdeGiac (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
The cover of issue 2 of the Journal is a graphic revisitation of Giacomo Verde's "non-profit antiportal website" X-8x8-X, an interactive installation dated November 1999 (Milan Triennale, TECHNE') and linked to the artivistic theme.